EPISTEMOLOGICAL THINKING ABOUT ACCOUNTING IN THE ERA OF ARTIFICIAL INTELLIGENCE - Friedrich, Marcos Paulo Albarello; Zanievicz, Marcia; Cadorna Venturini, Jonas; Eduardo Schuster, Wagner (Revista Gestão Organizacional, 2022)
Purpose: the objective of this study was to position accounting among the branches of human knowledge in order to understand the effects of these changes on it. The central line on which the discussion unfolds is what defines it as a science and whether, as a science, it can cease to exist. Method/approach: we adopted the Theoretical Essay as our methodology. Main findings: the future of accounting is a recent topic in several worldwide journals and there is a unanimous understanding that accounting will not cease to exist, it should only seek in essence its reason for existing to remain competitive in the face of automated processes, acting mainly in the creation, interpretation and data authentication and reporting for decision making and no more manual processes. This study explores the ways in which the accounting sciences will be able to remain at the forefront of knowledge and as a profession of high importance for organizations. Theoretical, practical/social contributions: the evolution of digital technologies such as Internet of Things (IoT), Big Data and Artificial Intelligence for business (BI) has provoked discussions about the future of professions, especially those that present data collection and processing activities. From this perspective, the essay contributes by directing the discussion to accounting and reflecting on the transformation of accounting science with increasing emphasis on report creation, interpretation, and authentication. Originality/relevance: the originality of the study lies in establishing links between accounting science and disruptive technologies.